2013
DOI: 10.1007/s10120-013-0249-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of 5-fluorouracil-induced cytotoxicity by leucovorin in 5-fluorouracil-resistant gastric cancer cells with upregulated expression of thymidylate synthase

Abstract: BackgroundElucidation of the mechanisms by which gastric cancer cells acquire resistance to 5-fluorouracil (5FU) may provide important clues to the development of effective chemotherapy for 5FU-resistant gastric cancerMethodsFour 5FU-resistant cell lines (MKN45/5FU, MKN74/5FU, NCI-N87/5FU, and KATOIII/5FU) were established by continuous exposure of the cells to progressively increasing concentrations of 5FU for about 1 year. Then, mRNA expression levels of four genes associated with 5FU metabolism, i.e., thymi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…High expression levels of survivin and TS are associated with chemoresistance (24,28). In the present study, it was found that combined 5-FU and GA treatment further decreased the RNA and protein levels of survivin and TS compared with either monotherapy, consistent with improved chemoresistance and enhanced anticancer effects.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…High expression levels of survivin and TS are associated with chemoresistance (24,28). In the present study, it was found that combined 5-FU and GA treatment further decreased the RNA and protein levels of survivin and TS compared with either monotherapy, consistent with improved chemoresistance and enhanced anticancer effects.…”
Section: Discussionsupporting
confidence: 68%
“…5-FU exerts cytotoxicity by inhibiting TS activity and interrupting DNA and RNA syntheses (27). High TS expression is also associated with 5-FU resistance (28) and poor prognosis (29).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of resistance to 5-FU, namely, enhanced activities of thymidylate synthase (TS) and dihydropyrimidine dehydrogenase (DPYD), are well known to endow cancer cells with resistance to 5-FU in vitro and in clinical studies (12)(13)(14)(15). Actually, 5-FU is used in combination with 5-chloro-2,4-dihydroxypyridine, which is a DPYD inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Different drugs may finally induce the MDR phenotype but through various signaling pathways, consequently leading to apparently different expression or functional changes of involved molecules. Previous studies have shown that several known proteins (such as P-glycoprotein, RhoE, GAS1, thymidylate synthase Bax and Bcl-2) play an important role in development of VCR-, 5-fluorouracil-or doxorubicin-based MDR phenotype gastric cancer cells (6,(28)(29)(30)(31), therefore, we speculate that different chemosensitizers may work through these known or some unknown ways to restore chemosensitivity of tumor MDR cells. Cisplatin, cis-diamminedichloroplatinum (CDDP), is deemed to be the 'penicillin of cancer drugs' due to its universal, early, and effective treatment for many cancers, including gastric cancer (32).…”
Section: Discussionmentioning
confidence: 82%